Immature gastric teratoma in a newborn - Sandheeah Ramdeny; Katherine Broad; Prabhu Sekaran; Sara Harrison; Philip Connor; Mallinath Chakraborty (Elsevier, 2019)
We present a full-term male infant with a palpable abdominal mass who presented with severe haematemesis associated with cardiovascular compromise. Although an initial ultrasound imaging identified a left supra-renal calcified mass suggesting a neuroblastoma, further imaging suggested an atypical mass which was separate from the spleen and left kidney. An upper gastro-intestinal contrast study localised the mass to the stomach and a computed tomograph suggested the possibility of a gastric teratoma likely in combination with a raised serum Alpha-fetoprotein. The mass was completely surgically resected, and histology confirmed an immature gastric teratoma.We would like to draw the attention of clinicians of the possibility of a gastric teratoma in an infant who presents with an abdominal mass and haematemesis.